2019
DOI: 10.1080/13668803.2019.1704398
|View full text |Cite
|
Sign up to set email alerts
|

How much would family and medical leave cost workers in the US? Racial/ethnic variation in economic hardship under unpaid and paid policies

Abstract: Using a capability approach, this study assesses economic constraints under the current US national unpaid family and medical leave (FML) policy compared to a hypothetical national paid FML policy for all full-year workers. Existing literature documents gender and class differences in barriers to FML use, but there is limited research on racial/ethnic minority workers. Our results indicate that if FML policy changed from unpaid to paid leave, black workers would gain a greater percentage of family income back … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Department of Labor, n.d.) and Latinx workers (Heymann et al, 2021). Though we did not collect race or ethnicity data for this study, others have identified FMLA eligibility criteria, in particular the requirement that a worker be employed for one year before accessing leave, as contributing to racial and socioeconomic disparities, disproportionately excluding Black, Indigenous, and multiracial families (Heymann et al, 2021), as well as low-income families, who are more likely to work for employers or in jobs that do not provide FMLA benefits (Joshi et al, 2020). A U.S. federal paid leave policy with fewer eligibility criteria would improve feasible and equitable access to time off for caregivers of CMC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Department of Labor, n.d.) and Latinx workers (Heymann et al, 2021). Though we did not collect race or ethnicity data for this study, others have identified FMLA eligibility criteria, in particular the requirement that a worker be employed for one year before accessing leave, as contributing to racial and socioeconomic disparities, disproportionately excluding Black, Indigenous, and multiracial families (Heymann et al, 2021), as well as low-income families, who are more likely to work for employers or in jobs that do not provide FMLA benefits (Joshi et al, 2020). A U.S. federal paid leave policy with fewer eligibility criteria would improve feasible and equitable access to time off for caregivers of CMC.…”
Section: Discussionmentioning
confidence: 99%
“…Wage and Hour Division, 2012). These eligibility requirements for businesses and workers contribute to disparities in access to the federal benefit, disproportionately excluding low-income workers as well as workers of color, particularly mothers of color (Baum & Ruhm, 2016; Brown & Medoff, 1989; Heymann et al, 2021; Horowitz, 2019; Joshi et al, 2020; Rossin-Slater et al, 2013; U.S. Department of Labor, n.d.).…”
mentioning
confidence: 99%
“…Both also support healthy child development, although for childcare subsidies, positive effects depend on the quality of the care (Johnson, Martin, and Ryan 2014). Burgeoning research shows that paid family and medical leave programs and childcare subsidies reduce the high costs of unpaid leave and childcare, yet are not equally accessible for black, Hispanic, and immigrant families due to affordability constraints (Baldiga et al 2018;Joshi et al 2019), lower take-up rates (Acevedo-Garcia et al 2021b;Rossin-Slater, Ruhm, and Waldfogel 2013), more limited knowledge about programs (Alvira-Hammond and Gennetian 2015; Goodman, Elser, and Dow 2020); eligibility rules (Acevedo-Garcia et al 2021b;Joshi et al 2020); and administrative burden like extensive application documentation, interim reporting, and benefit or leave reassessments (Adams and Matthews 2013; U.S. Department of Labor 1993).…”
Section: Discussionmentioning
confidence: 99%
“…16. Joshi et al (2019) also provide an assessment of the cost to the U.S. of providing paid family and medical leave, with an emphasis on potential racial and ethnic disparities. the U.S. deficit over the 2020-2030 budget window.…”
Section: Paid Sick Leave Coverage and Utilizationmentioning
confidence: 99%